Effect of Capacitive Radiofrequency on the Fibrosis of Patients with Cellulite - Rodrigo Marcel Valentim da Silva; Priscila Arend Barichello; Melyssa Lima Medeiros; Waléria Cristina Miranda de Mendonça; Jung Siung Camel Dantas; Oscar Ariel Ronzio; Patricia Meyer Froes; Hassan Galadari (Hindawi Limited, 2013)
Background. Cellulite is a type of lipodystrophy that develops primarily from an alteration in blood circulation or of the lymphatic system that causes structural changes in subcutaneous adipose tissue, collagen, and adjacent proteoglycans. The radiofrequency devices used for cutaneous applications have shown different physiological treatment effects, but there is controversy about the suitable parameters for this type of treatment. Objectives. The aim of this study was to evaluate the effects of low-temperature radiofrequency to confirm the thinning of the collagen tissue and interlobular septa and consequent improvement of cellulite. Methods. A sample of eight women was used to collect ultrasonographic data with a 12 MHz probe that measured collagen fiber thickness. The Vip Electromedicina (Argentina) device, frequency of 0.55 MHz and active electrode 3.5 cm in diameter (area = 9.61 cm2), was applied to a 10 cm2 region of the gluteal region for 2 minutes per area of active electrode, during 10 biweekly sessions. Results. The Wilcoxon matched paired test was applied using GraphPad InStat 3.01 for Win95-NT software. Pre- and posttreatment mean collagen fiber thickness showed a 24.66% reduction from 1.01 to 0.67 mm. Statistical analysis using the Wilcoxon matched paired test obtained a significant two-tailed P value of 0.0391. Conclusion. It was concluded that the use of more comfortable temperatures favored a reduction in fibrous septum thickness and consequent cellulite improvement, evidenced by the lower degree of severity and decrease in interlobular septal thickness.